Cardiomyocyte generation from somatic sources — current status and future directions. (August 2016) - Monaghan, Michael G; Holeiter, Monika; Layland, Shannon L; Schenke-Layland, Katja
Graphical abstract: Direct reprogramming of fibroblasts to a functional cardiomyocyte with or without a progenitor cell intermediate has been widely reported with increasing efficiencies using transcription factors, miRs and small molecules. The evolution of these protocols will benefit greatly by the use of cardio-stimulatory environments with biomaterials, extracellular matrices and dynamic cultures based on lessons learned in vivo, which could yield significant efficiencies suitable for implantation. Additionally, using delivery vehicles of transdifferentiation factors that are based on biomaterial and extracellular matrices, which are favourable towards cardiomyogenesis could further improve direct reprogramming in vivo . Highlights: Capturing the current status of cardiomyocyte direct reprogramming. The epigenetic heritage of cells is important for transdifferentiation. Wiping the starting cell's epigenetic memory enhances transdifferentiation. Small molecules are emerging as potent activators of cell transdifferentiation. The incorporation of biomaterials and mechanics will improve transdifferentiation. Abstract : Transdifferentiation of one cell type to another has garnered significant research efforts in recent years. As cardiomyocyte loss following myocardial infarction becomes debilitating for cardiac patients, the option of an autologous source of cardiomyocytes not derived from multi/pluripotent stem cell sources is an attractive option. Such direct programming has been clearly realized with the use of transcription factors, microRNAs and more recently small molecule delivery to enhance epigenetic modifications, all albeit with low efficiencies in vitro . In this review, we aim to present a brief overview of the current in vitro and in vivo transdifferentiation strategies in the generation of cardiomyocytes from somatic sources. The interdisciplinary fields of tissue, cell, material and regenerative engineering offer many opportunities to synergistically achieve directly programmed cardiac tissue in vitro and enhance transdifferentiation in vivo . This review aims to present a concise outlook on this topic with these fields in mind.